DNA profiling and DNA fingerprinting - Epplen, Jörg T; Lubjuhn, Thomas (Birkhäuser, 1999)
Ruhr-Universitat Bochum, Germany. Presents practical approaches to answering biological and medical questions using DNA fingerprinting and genetic profiling. Includes statistical evaluation of the data. For students and researchers in biochemistry, biology, and genetics. Plastic-comb binding, hardcover also available.
Methods and tools in biosciences and medicine
Keywords: DNA fingerprinting; soudní lékařství; DNA Fingerprinting; genetika, lékařská genetika